Effect of six weeks ubiquinol supplementation on mitochondrial respiratory function and exercise capacity in healthy males - Jarred P. Acton; Nehal S. Alsharif; Jack W. Bond; Stuart P. Cocksedge; Abbie G. Mclellan; Donald L. Peden; Mark P. Funnell; Hannah F. Dugdale; Lewis J. James; Richard A. Ferguson; Tom Clifford; Stephen J. Bailey (European Journal of Applied Physiology, 2026)
Coenzyme Q10 (CoQ 10 ) is an integral component of the mitochondrial electron transfer system. Most studies have administered the oxidised form of CoQ 10 (ubiquinone) and observed no effects on mitochondrial respiratory function or endurance exercise performance. The reduced form of CoQ 10 , ubiquinol (UQH 2 ), has greater bioavailability than ubiquinone, but the effects of UQH 2 supplementation on mitochondrial respiratory function and exercise capacity are unclear. Fifty-four healthy, recreationally active males were randomised to receive either 300 mg·day − 1 UQH 2 or placebo (PLA) for 6 weeks in a double-blind independent-group design. Before and after the supplementation period, skeletal muscle mitochondrial respiration variables and protein content of the mitochondrial leak proteins, adenine nucleotide translocase1 + 2 (ANT1 + 2) and uncoupling protein-3 (UCP-3), were assessed. In addition, participants completed a severe-intensity cycle test to exhaustion to assess time to the limit of tolerance (T Lim ) and oxygen uptake (V̇O 2 ) kinetics. Compared to pre-supplementation and PLA, UQH 2 supplementation increased plasma [CoQ 10 ] ( P < 0.05), and lowered inverse respiratory control ratio (Pre-PLA: 0.064 ± 0.034 vs. Post-PLA: 0.072 ± 0.026; Pre- UQH 2 : 0.073 ± 0.039 vs. Post-UQH 2 : 0.044 ± 0.019; P < 0.05), suggestive of improved oxidative phosphorylation coupling efficiency. There were no differences in ANT1 + 2 or UCP-3 protein content post-supplementation compared to pre-supplementation between groups ( P > 0.05). End-exercise V̇O 2 , change in V̇O 2 between 2 min and end-exercise, and T Lim were not different between groups post-supplementation ( P > 0.05). Six-weeks UQH 2 supplementation increased plasma [CoQ 10 ] and oxidative phosphorylation coupling efficiency, but did not alter mitochondrial leak proteins, T Lim or V̇O 2 kinetics during severe-intensity exercise in healthy, active males.